Dual DNMT–EZH2 Inhibition as a Stroma-Directed Strategy in Castration-Resistant Prostate Cancer: A Commentary - Rongxin Chang; Guodong Liu (Serican Journal of Medicine, 2026)
Background: Castration-resistant prostate cancer (CRPC) remains a lethal progression state despite androgen-deprivation therapy, driven by epigenetic plasticity and a fibrotic tumour microenvironment. Single-agent epigenetic inhibitors have limited activity in solid tumours, partly because compensatory H3K27me3-mediated silencing may preserve gene repression after DNMT inhibition. Objective: To comment on a recent PNAS study and evaluate the mechanistic and translational rationale for dual DNMT–EZH2 inhibition as a stroma-directed strategy in CRPC. Discussion: The study shows that DNMT-inhibitor monotherapy induces compensatory EZH2-dependent H3K27me3 deposition at the ADAMTS1 locus, maintaining silencing of this collagenase. Dual DNMT–EZH2 targeting reactivates ADAMTS1, promotes collagenolysis, and disrupts FAK/MAPK/EMT mechanotransduction, thereby counteracting androgen-independent survival. In immunocompetent preclinical models, the combination achieves over 90% tumour suppression, increases CD8⁺ T-cell infiltration by 11.4-fold, reduces immunosuppressive cells, and activates interferon-driven innate immune pathways with limited systemic toxicity. Conclusion: Dual DNMT–EZH2 inhibition is a mechanistically justified preclinical strategy that links epigenetic reprogramming, ECM remodelling, and anti-tumour immunity. Clinical validation, biomarker development, and assessment of immune-checkpoint combinations are needed before translation.